A Online Teaching Experience as a Member of International Faculty during the Outbreak of COVID-19 in China (Comparative & International Education Series, 2021)
This paper presents a digital autoethnographic investigation of a new international faculty member who instructed three global education courses via online at Shanghai International Studies University, China. By drawing on insights from Pierre Bourdieu’s sociological and pedagogic theories, this paper provides five primary scholarly conversations: (a) Institutional Context: Shanghai International Studies University (SISU); (b) The Initial Impact of COVID-19 on the SISU Community; (c) Challenges for Course Preparation: Anxiety, Frustration, and Uncertainties; (d) Language and Technological Barriers in the New E-learning Platforms; and (e) Factors Hindering the Effectiveness of E-learning. Notably, there were some potential social justice issues identified via online courses, hampering students from using the internet and equipment due to their socio-economic circumstances. Therefore, this paper calls on academics and educational policymakers to pay more attention to these issues and find avenues for students’ academic success regardless of any socio-economic status and socio-cultural background.